Konsep Dan Penerapan Green Computing di Lingkungan Kampus - Pracasitaram, I Gede Made Surya Bumi; L, Linawati; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2019)
The development of information technology to help increase activities also brings enormous progress in the world of Education, the development of information technology involves also the negative environment such as increasing the energy needs needed, which electricity needs in Indonesia Power plants use non-renewable energy as a fossil energy. To reduce energy use in the campus environment in this study using the concept of green computing . Green computing is the study and practice of environmentally sustainable computing or IT. It is expected that the application of green computing can streamline and save energy usage in the campus environment and reduce negative impacts on the environment. Keywords — Computer, Energy Efficiency, Green computing.